A SEMANTIC ANALYSIS ON THE JAVANESE WORD “JAJAN” AS USED BY “SUARA AKBAR” RADIO LISTENER IN JEMBER - Ageng Soeharno; Habibatul Azizah Al Faruq (Universitas Muhammadiyah Jember, 2021)
Indonesian is a very rich language originating from various regional languages throughout Indonesia which stretches from Sabang to Merauke. Of the 668 regional languages in Indonesia, there are several regional languages that are very influential for the development of the Indonesian language to date.Javanese is one of the languages that has the most influence on Indonesian vocabulary, in addition to Malay, Banjarese, Manadonese, Sasak, Sundanese, Bugis, and other regional languages.Javanese is the first language of the Javanese population living in Central Java Province, Special Region of Jogjakarta, East Java, Banten, Lampung, around Medan, transmigration areas in Indonesia, among others, parts of Riau, Jambi, Central Kalimantan, and several places in Indonesia. abroad, namely Suriname, the Netherlands, New Caledonia, and the West Coast of JohorThe scope of this research covers the entire area of the city of Jember which is covered by the “Suara Akbar” radio wave on the 94.6 FM frequency.This study uses qualitative methods. The data used are sourced from or obtained through interviews, field notes, personal notes and other official documents.